Histopathological study of the effects of administering heme iron and ferrous sulfate with vitamin C in rat liver and brain - Guija-Poma, Emilio (2019)
Objective: To determine the effect exerted by the administration of heme iron and ferrous sulfate with vitamin C in rat liver and brain. Materials and methods: The study used Holtzman albino rats housed in a bioterium with a temperature of 22 ± 2 °C, humidity between 50 and 70 %, and 12 hours of light and 12 hours of darkness. They received elemental iron 4.0 mg/kg b.w. as heme iron or ferrous sulfate + vitamin C 10 mg for seven days, at which time they were sacrificed, and blood, liver and brain were extracted. Histological sections were made and treated with hematoxylin-eosin for microscopic observation, and serum antioxidant capacity was measured. Results: The brains of the rats treated with heme iron and ferrous sulfate + vitamin C did not undergo significant changes, while the histological sections of the livers of the rats treated with heme iron showed a parenchyma without polar distribution, some nuclei lacking cytoplasm and numerous Küpffer cells at the sinusoidal level. In contrast, the rats treated with ferrous sulfate + vitamin C had a significantly deteriorated hepatic parenchyma, some areas with loose nuclei without cytoplasm and others with disappeared cytoplasmic membranes. In addition, in some areas, the liver parenchyma was homogenized. Conclusions: The brains of the rats treated with heme iron and those with ferrous sulfate + vitamin C did not practically undergo any change. In contrast, the liver of the rats treated with ferrous sulfate + vitamin C had greater liver damage than those treated with heme iron.